Contributions to Celtiberian Etymology II (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
New etymologies for two Celtib. words are proposed. For albana [K.1.3, –2], a derivation from Proto-Celtic *anmana ‘names’ is suggested and the related question of the variation between lenited b and m is discussed in typological comparison with Irish.  The final  word of Botorrita I  ruzimuz [K.1.1, A–11] is explained as a nominal derivative in -mo- of the Celtic verbal stem *rudī- ‘to become red’.